ICT, Good Governance, and Development - Jindal, Neena; Kishtwal, Ashok; Sehrawat, Anil (Indian Journal of Computer Science, 2016)
E-governance demand is increasing rapidly in the whole world. India is also not an exception to this demand. The main aim of egovernance is to nourish good governance through information communication and technology (ICT) and widening the participation of public. As we know, people in developing countries are living at the minimum cost of 1 per day, so, with the establishment of ICT it can be seen that the goals of good governance can be achieved. E-governance has no magical trick to achieve this. To strengthen the effective, efficient and transparent government system, the plan of action of ICT has been initiated to enhance the condition of the country. The present article is an attempt to examine the significance of e-governance in refreshing good governance.